MEAT PRODUCTION BY STEERS OF DIFFERENT GEOTYPES - & et al., Velmatov (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The objective of this study to investigate meat production by steers of different genotypes. In order to study the productivity of Simmental and black and white Simmental x Holstein cross bred, steers, six groups of bull-calves with 15 animals each, were formed. The first group consisted of Simmental steers, the second group (3/8) blooded, the third group (1/2) blooded, the fourth group (5/8) blooded, the fifth group (3/4) blooded and the sixth group (7/8) blooded Holstein steers respectively. Under the same conditions of feeding and maintenance purebred Simmental animals grow more intensively. At 18-months of age they exceed (3/8) Holstein blooded bull calves by 6.2 kg, half blooded by 16.5 kg, (5/8) blooded by 18.4 kg, (3/4) blooded by 25 kg and (7/8) blooded by 35.2 kg (Р <0,001). The slaughter weight of Simmental bulls surpass their counterparts by 7.4-24.8 kg. Significant differences were observed (p < 0.001) between Simmental and crossed bull-calves having in their genotype 75.0-87.5% of Holsteins blood were observed. The same level of reliability (P <0.01) was indicated in the mass of internal fat and slaughtered yield. The specific gravity of flesh in bull calves carcass of all studied groups varied within the limits of 78.7-80.6%.The mass of the flesh of Simmental bulls was higher than hybrid animals by 4.0-12.0 kg.The fat content in meat of Simmental bull calves is 9.10%, that is 1,86-2,31% more than hybrid steers. Concerning to the protein content, the crossed bulls exceeded the Simmental ones by 0.10-0.39%.